Selection of reference genes for RT-qPCR studies in blood of beluga whales (Delphinapterus leucas) - I-Hua Chen; Jiann-Hsiung Wang; Shih-Jen Chou; Yeong-Huey Wu; Tsung-Hsien Li; Ming-Yih Leu; Wen-Been Chang; Wei Cheng Yang (PeerJ, 2016)
Reverse transcription quantitative PCR (RT-qPCR) is used for research in gene expression, and it is vital to choose appropriate housekeeping genes (HKGs) as reference genes to obtain correct results. The purpose of this study is to determine stably expressed HKGs in blood of beluga whales (Delphinapterus leucas) that can be the appropriate reference genes in relative quantification in gene expression research. Sixty blood samples were taken from four beluga whales. Thirteen candidate HKGs (ACTB, B2M, GAPDH, HPRT1, LDHB, PGK1, RPL4, RPL8, RPL18, RPS9, RPS18, TFRC, YWHAZ) were tested using RT-qPCR. The stability values of the HKGs were determined by four different algorithms. Comprehensive analysis of the results revealed that RPL4, PGK1 and ACTB are strongly recommended for use in future RT-qPCR studies in beluga blood samples. This research provides recommendation of reference gene selection, which may contribute to further mRNA relative quantification research in the peripheral blood leukocytes in captive cetaceans. The gene expression assessment of the immune components in blood have the potential to serve as an important approach to evaluating cetacean health influenced by environmental insults.